Mission Accomplished? We Need a Guide to the 'Post Release' World of Wolbachia for Aedes-borne Disease Control. Issue 3 (March 2018) - Ritchie, Scott A.; van den Hurk, Andrew F.; Smout, Michael J.; Staunton, Kyran M.; Hoffmann, Ary A.
Abstract : Historically, sustained control of Aedes aegypti, the vector of dengue, chikungunya, yellow fever, and Zika viruses, has been largely ineffective. Subsequently, two novel 'rear and release' control strategies utilizing mosquitoes infected with Wolbachia are currently being developed and deployed widely. In the incompatible insect technique, male Aedes mosquitoes, infected with Wolbachia, suppress populations through unproductive mating. In the transinfection strategy, both male and female Wolbachia -infected Ae. aegypti mosquitoes rapidly infect the wild population with Wolbachia, blocking virus transmission. It is critical to monitor the long-term stability of Wolbachia in host populations, and also the ability of this bacterium to continually inhibit virus transmission. Ongoing release and monitoring programs must be future-proofed should political support weaken when these vectors are successfully controlled. Highlights: The use of Wolbachia to control populations of Ae. aegypti mosquitoes, and to reduce transmission of dengue, Zika, and other Aedes -borne disease viruses, is growing rapidly. Transinfection that introduces virus-blocking w Mel Wolbachia into Ae. aegypti is leading the way, with operational releases in ten countries. The use of Wolbachia to effectively induce male sterility is being used to reduce populations of Ae. aegypti, Aedes polynesiensis, and Aedes albopictus in several international programs. The scale-up of 'rear and release' Wolbachia programs requires large mosquito-rearing capacity to effectively target large urban areas subject to Aedes -borne viruses. Thus, these programs have evolved from relatively small university- and government-based research programs into large industrialised programs funded by large corporations. The emphasis has been focussed on establishing Wolbachia transinfection and incompatible insect technique (IIT) programs, with little planning of 'after release' strategies to sustain Wolbachia infections or population-reduction effectiveness.